2018
DOI: 10.5194/angeo-36-509-2018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of subauroral polarization streams on the mid-latitude thermospheric disturbance neutral winds: a universal time effect

Abstract: Abstract. The temporal and spatial variations in thermospheric neutral winds at an altitude of 400 km in response to subauroral polarization streams (SAPS) are investigated using global ionosphere and thermosphere model simulations under the southward interplanetary magnetic field (IMF) condition. During SAPS periods the westward neutral winds in the subauroral latitudes are greatly strengthened at dusk. This is due to the ion drag effect, through which SAPS can accelerate neutral winds in the westward directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…Enhanced westward winds are found to peak around the same latitude as SAPS flows from comparisons between ion drift and neutral wind measurements (Wang et al, , ). Different forces have been suggested to explain the acceleration of neutral wind, involving, for example, the ion drag force in the aurora zone (Wang et al, ) and on a global scale (Wang et al, ), the Coriolis force (Lühr et al, ; S.‐R. Zhang et al, ), and pressure gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced westward winds are found to peak around the same latitude as SAPS flows from comparisons between ion drift and neutral wind measurements (Wang et al, , ). Different forces have been suggested to explain the acceleration of neutral wind, involving, for example, the ion drag force in the aurora zone (Wang et al, ) and on a global scale (Wang et al, ), the Coriolis force (Lühr et al, ; S.‐R. Zhang et al, ), and pressure gradient.…”
Section: Introductionmentioning
confidence: 99%
“…This difference is related to the molecular viscosity in the thermospheric composition. Furthermore, as disclosed in Wang H et al (2018), the westward winds at sector of 12-24 MLT due to SAPS will not disappear at the time that the SAPS close. On the contrary, the winds will last several hours because of inertial forces, owing to the dense thermospheric density (Wang H et al, 2018).…”
Section: Ut Variations Of Poleward Winds Driven By Sapsmentioning
confidence: 92%
“…Therefore UT variations in the responses of thermospheric winds to SAPS are really within expectations; however, delineation of the relative importance among those competing forcings responsible for longitudinal/UT variations remains a matter of significant scientific interest. Using GITM simulations, Wang H et al (2018) investigated the zonal wind response to SAPS that occurred at different UTs. They found that the westward wind disturbances exhibited a significant UT variation; the disturbances reached their maxima (minima) at 18 (04) UT and 04 (16) UT in the Northern and Southern Hemisphere, respectively.…”
Section: At Subauroral Latitudes Subauroral Polarization Streams (Saps)mentioning
confidence: 99%
“…Wang H et al (2018) investigated the temporal and spatial variations of thermospheric neutral winds at 400 km altitude under the influence of subauroral polarization streams (SAPS) based on simulations of the global ionosphere and thermosphere model (GITM). During SAPS periods under southward IMF conditions, the westward neutral winds at subauroral latitudes are greatly strengthened at dusk.…”
Section: Ionospheric Dynamics and Couplingsmentioning
confidence: 99%